2016
DOI: 10.1111/ddi.12462
|View full text |Cite
|
Sign up to set email alerts
|

A global assessment of alien amphibian impacts in a formal framework

Abstract: Aims The environmental and socio‐economic impacts of alien species need to be quantified in a way that makes impacts comparable. This allows managers to prioritize their control or removal based on impact scores that can be easily interpreted. Here we aim to score impacts of all known alien amphibians, compare them to other taxonomic groups and determine the magnitude of their ecological and socio‐economic impacts and how these scores relate to key traits. Location Global. Methods We used the generic impact sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
106
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 75 publications
(110 citation statements)
references
References 65 publications
2
106
0
Order By: Relevance
“…A full reference list can be found in Measey et al (2016). We found that both EICAT and GISS maximum score were not related to the number of publications found on the species' impacts (Kendall's tau = 0.24 and 0.25; P = 0.059 and 0.055 respectively; Figure 2).…”
Section: Resultsmentioning
confidence: 87%
See 4 more Smart Citations
“…A full reference list can be found in Measey et al (2016). We found that both EICAT and GISS maximum score were not related to the number of publications found on the species' impacts (Kendall's tau = 0.24 and 0.25; P = 0.059 and 0.055 respectively; Figure 2).…”
Section: Resultsmentioning
confidence: 87%
“…The formulation in GISS of a maximum disease impact (see Nentwig et al 2016) leaves room for different assessors to score different impacts, based on their interpretation, which might have led to a high score in GISS and a MO in EICAT. Given the severity of the effects of Batrachochytrium dendrobatidis and other diseases, both EICAT and GISS appear to highlight the difficulty of assigning the spread of disease through alien taxa and the transmission thereof to native species (see also Measey et al 2016, Evans et al 2016, although this is widely acknowledged in amphibians (Fisher and Garner 2007).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations